EFFECTS OF LASER THERAPY, LOW-LEVEL ON INDUCED CONTRACTION OF WOUNDS IN RATS WISTAR (Fiep Bulletin - online, 2011)
The process of wound healing consists of a complex series of stages, independent and simultaneous. The aim of this study is to evaluate the healing effect of different doses of lasers InGAP, the contraction of skin wounds surgically induced in male Wistar rats. We used 18 animals, 56 days, weight 300g and measuring 17cm in middle ear to the beginning of the tail, divided into 3 groups of 6 animals. The group I control (no treatment), the 4 J / cm ² Group II, and the Group III 8 J / cm², applications were daily for 15 consecutive days, were performed euthanasia on the 7th and 15th day, the area of the wounds were photographed and measured by software QUANTIPORO. It was performed variance analysis, Tukey post hoc, and the significance level of 5% using the Genes software 2006.The wound contraction for the day 15 results were not significant, but, by analyzing the time corresponding to 7 to 15 day, the group treated with a dose of 4 J/cm² obtained a better response suggesting that laser therapy works in a specific phase of the process of wound healing.
Keywords: Wound healing; low-intensity laser; wound contraction